Prediction of postoperative inflammatory complications after esophageal cancer surgery based on early changes in the C-reactive protein level in patients who received perioperative steroid therapy and enhanced recovery after surgery care: a retrospective analysis - Kazuki Kano; Toru Aoyama; Tetsushi Nakajima; Yukio Maezawa; Tsutomu Hayashi; Takanobu Yamada; Tsutomu Sato; Takashi Oshima; Yasushi Rino; Munetaka Masuda; Haruhiko Cho; Takaki Yoshikawa; et al. (BMC Cancer, 2017)
Abstract Background Serum C-reactive protein (CRP) level can be an indicator of the early stage of infectious complications. However, its utility in advanced esophageal cancer patients who receive radical esophagectomy with two- or three-field lymph node dissection with perioperative steroid therapy and enhanced recovery after surgery (ERAS) care is unclear. Methods The present study retrospectively examined 117 consecutive esophageal cancer patients who received neoadjuvant chemotherapy followed by radical esophagectomy. All patients received perioperative steroid therapy and ERAS care. The utility of the CRP value in the early detection of serious infectious complications (SICs) was evaluated based on the area under the receiver operating characteristic curve (AUC). Univariate and multivariate logistic regression analyses were performed to identify the risk factors for SICs. Results SICs were observed in 20 patients (17.1%). The CRP level on postoperative day (POD) 4 had superior diagnostic accuracy for SICs (AUC 0.778). The cut-off value for CRP was determined to be 4.0 mg/dl. A multivariate analysis identified CRP ≥ 4.0 mg/dl on POD 4 (odds ratio, 18.600; 95% confidence interval [CI], 4.610–75.200) and three-field lymph node dissection (odds ratio, 7.950; 95% CI, 1.900–33.400) as independent predictive factors. Conclusions CRP value on POD 4 may be useful for predicting SICs in esophageal cancer patients who receive radical esophagectomy with perioperative steroid therapy and ERAS care. This result may encourage the performance of imaging studies to detect the focus and thereby lead to the early medical and/or surgical intervention to improve short-term outcomes.